2012
DOI: 10.1111/j.1476-5381.2012.01886.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide‐induced mechanical hyperalgesia and allodynia require activation of both Cav3.2 and TRPA1 channels in mice

Abstract: Keywordstransient receptor potential ankyrin-1 (TRPA1); Cav3.2; T-type calcium channel; hydrogen sulfide; pain; hyperalgesia; allodynia BACKGROUND AND PURPOSEHydrogen sulfide, a gasotransmitter, facilitates somatic pain signals via activation of Cav3.2 T-type calcium channels in rats. Given evidence for the activation of transient receptor potential ankyrin-1 (TRPA1) channels by H2S, we asked whether TRPA1 channels, in addition to Cav3.2 channels, contribute to the H2S-induced mechanical hyperalgesia and allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
59
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 26 publications
5
59
0
Order By: Relevance
“…Our algesia in rats (2) and mice (8,9). These findings are in agreement with the recent evidence that Ca v 3.2, among the three isoforms of T-type Ca 2+ channels, in the sensory neurons plays a major role in processing of somatic (11) and visceral pain (12).…”
supporting
confidence: 81%
See 4 more Smart Citations
“…Our algesia in rats (2) and mice (8,9). These findings are in agreement with the recent evidence that Ca v 3.2, among the three isoforms of T-type Ca 2+ channels, in the sensory neurons plays a major role in processing of somatic (11) and visceral pain (12).…”
supporting
confidence: 81%
“…On the other hand, TRPA1 is now considered a target for H 2 S (8). Our latest study has shown that the activation of TRPA1 in addition to Ca v 3.2 is required for the H 2 Sinduced somatic pain (9). Similarly, the present findings suggest that the H 2 S-induced colonic pain and referred hyperalgesia are also dependent on activation of TRPA1.…”
supporting
confidence: 65%
See 3 more Smart Citations